KOSAKATA ARKAIS DALAM BAHASA MELAYU DIALEK SAMBAS - Andre Andre; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research on archaic vocabulary in Malay Sambas dialect aims to find out the archaic status, lingul unit form of archaic vocabulary and lexical meaning of archaic vocabulary. This study uses a descriptive method in the form of mixing methods. Data collection techniques are documentary studies, interviews, and questionnaires. This research resulted in 32 archaic words for adolescents, 18 archaic words for adults, 11 archaic words for the elderly and 25 archaic words for all age groups, 23 archaic words for male gender and 27 archaic words for gender. woman. The form of the lingual unit is focused on data on the archaic status of all age groups with a total of 72 words, so that the lingual unit form found consists of 41 words of monomorphism in the form of nouns, 18 words of verbs, 4 words of adjectives and 3 words of numerals. The polymorphism in the form of affixation is 2 words, reduplication is 1 word. As for the noun phrase as much as 1 word and 1 word adjective. The lexical meaning was focused on the archaic status data from all ages, so that 72 lexical meanings were obtained.Keywords: Archaic, Language, Malay Sambas, Vocabulary